Decision Support System Promotion Criteria For Increasing Sales of Randang Minang Hj. Fatimah Uses Fuzzy Sugeno - S Silvilestari (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Decision support system (DSS) is a system that is able to assist in making decisions from various types of choices that are made accurately and in accordance with the desired goals. Many case problems can be solved using a decision support system including the criteria for increasing sales of Rendang Hj. Fatimah in the Solok City area. The problem that occurs is the lack of promotional criteria in marketing Rendang products so that information is less affordable to consumers. The purpose of this research is to increase the price of lace sales spread throughout Indonesia. Promotion criteria that will be improved such as, Price, Taste, Package, and Size. This research uses the Sugeno method, there are 4 ways the Tsukamoto method works, namely, Fuzification, Formation of Knowledge Base (Rule in the form of IF THEN), inference engine and defuzification, the operator used is the AND operator. Output results are at Rang 1 with Output Increase